India - Mynmar Political Relations from the Independence of India to the Present Time: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India and Mynmar are such countries which have been fast neighbors for a long time. India shares about 1643 km border with its north-eastern neighbor Myanmar. This very long border touches four out of seven north east states of India. Myanmar is thought to be a natural Land Bridge between South and Southeast Asian regions. India and Mynmar are closer to each other Physically, Culturally and historically but not politically. The basic thrust of the paper is in exploring progress on the political front having the launch of Look East Policy by India as a starting point and what it has in store for the future of these countries.